Relación de la ejecución presupuestaria y el reconocimiento a la ejecución de inversiones en la Municipalidad de Trompeteros 2019 – 2022 - Uriona Rodríguez, José Luís (2024)
The municipalities in the department of Loreto, at the end of the 2019 fiscal year, 35 of the 53 municipalities met the goals established by the Recognition of Investment Execution (REI); At the end of 2020, 29 of the 53 municipalities met the investment execution goals; for that year, the entity under study did not meet these goals. The objective of this research is to determine the relationship between budget execution and the REI in the district municipality of Trompeteros 2019 - 2022. This research work is Quantitative, Descriptive - Correlational level and Non-Experimental in design. In relation to the execution of investment expenses by Sub Generic Expenses accumulated 2019 – 2022, the Construction of Buildings and Structures were executed 64.66%; 53.71% of the Acquisitions of Vehicles, Machinery and Others were executed; and Intangible Investments were executed 94.99% Likewise, the results of the REI during the study period decreased, receiving only S/ 180,813. As well, it was determined that there is a direct relationship between the execution of investment expenses with the REI. Concluding that budget execution in investment expenses is low (65.31%), the incentives received for meeting goals were only achieved in 2019 and 2022 and there is a high degree of relationship between investment expenses and the REI.